Formulation and Physical Stability Testing of Chitosan Gel from Vaname Shrimp Shell (Litopenaeus Vannamei) with Carbopol 940 Gelling Agent - Norisca Aliza Putriana; Taofik Rusdiana; M. Abdul Aziz Prakoso (Universitas Padjadjaran (Unpad), 2019)
Wound is defined as a disorder of normal anatomy and skin’s function that occurs as a result of tissue injury or patalogic process resulting in epithelium discontinuity, with or without lossing underlying connective tissue. The use of chitosan in medicine, especially in surgery, gives many advantages in terms of wound healing that stimulates hemostasis of cell. Chitosan gel is one of the alternative wound treatments that still needs improvement, especially in terms of the effectiveness of the formulation. In this study, the physical stability of chitosan gel formulations was tested in various concentration of carbopol 940 as a gelling agent i.e, 0,5%, 1% and 1,5%. The parameters observed during the physical stability testing of this gel research were pH, viscosity, spreadability, homogeneity, organoleptic and sineresis gel. The result of the physical stability testing of chitosan gel stored for 56 days showed that formula 1 has the best result according to all parameters. Formula 1 has pH 5,8-6,2 at 25oC and 40oC, the best organoleptic stability, viscosity shift 9% at 25oC and 13,8% at 40oC, spreadability shift 10,9% at 25oC and 14,4% at 40oC. The best chitosan gel formulation for physical stability testing is chitosan gel with carbopol 940 concentration of 0.5%Keywords: Wound, Chitosan gel, Physical Stability